Hospital Ministry Under Coronavirus Lockdown - Cristobal, Geronimo (Archīum Ateneo, 2020)
My father; Gerry; is a veteran missionary for a small local Christian congregation in the Philippines that has held Sunday service at a hospital for the last fourteen years. Assisted by my mother Beth; he has done missionary work in various workplaces since the 1980s. His current post in the Palliative Care Unit; an office specializing in care to the chronically and terminally ill of the National Kidney and Transplant Institute (NKTI) in Metro Manila; puts him in proximity with frontline workers and patients during the current COVID-19 pandemic.